2015
DOI: 10.1016/j.cct.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of periodontal disease on outcomes in diabetes

Abstract: The prevalence of periodontal disease (POD) among adults aged 30 years and older in the United States is reported to be more than 47%, with higher prevalence seen among patients with diabetes mellitus (DM). POD has been associated with systemic inflammation, a known risk factor for cardiovascular and bone disease, both of which are more common in patients with DM. However, there is mixed evidence that treatment of POD reduces inflammation, improves DM control, and reduces DM complications. Our study objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
12
0
2
Order By: Relevance
“…Studies have shown that diabetic patients with periodontal infection have a higher risk of losing control of their glycemic condition; and this deteriorates over the long term compared to diabetic patients who do not suffer POD [3032]. In the course of periodontal disease, various proinflammatory mediators occur, such as interleukin- (IL-) 1, IL-6, and IL-8, IFN- γ , CCL5, TNF- α , prostaglandins, and metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that diabetic patients with periodontal infection have a higher risk of losing control of their glycemic condition; and this deteriorates over the long term compared to diabetic patients who do not suffer POD [3032]. In the course of periodontal disease, various proinflammatory mediators occur, such as interleukin- (IL-) 1, IL-6, and IL-8, IFN- γ , CCL5, TNF- α , prostaglandins, and metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…The details of our study methods have been published previously [8] . In summary, this was a cross-sectional study of all patients with diabetes presenting for their routine care at a university outpatient clinic.…”
Section: Methodsmentioning
confidence: 99%
“…Using a 48-item investigator-administered questionnaire [8] , all subjects were interviewed to obtain information about their age, gender, body mass index (BMI), diabetes history (onset, use of insulin), diabetes control and complications (A1c, retinopathy, neuropathy, nephropathy, heart attack, stroke), dental care history (last visit to dentist, frequency of brushing, flossing and use of mouthwash), dental problems (loose teeth, bleeding while brushing, teeth sensitivity and number of teeth) and presence of osteoporosis (treatment for or history of osteoporotic fracture). We manually counted their teeth, and all questionnaire responses regarding the above clinical variables were verified from the patient's clinic chart.…”
Section: Methodsmentioning
confidence: 99%
“…Prospective participants were screened with an investigator-administered questionnaire 19 to determine their eligibility. Patients with responses suggestive of POD who met inclusion criteria and agreed to participate in the study were referred for a full dental examination to confirm presence of POD.…”
Section: Methodsmentioning
confidence: 99%